DIGITALIZATION AND GLOBALIZATION: TRANSFORMATION OF UMKM IN THE DIGITAL ERA - Radjagukguk, Djudjur; Rusadi, Udi (Universitas Nasional, 2025)
Digitalization and globalization are reshaping the global business landscape, presenting both challenges and opportunities for Micro, Small, and Medium Enterprises (UMKM), which serve as economic pillars in developing countries. This study examines how UMKM adopt new technologies and adapt to the evolving global business environment, utilizing Innovation Diffusion Theory and Media Ecology Theory as analytical frameworks. A systematic literature review was conducted, synthesizing insights from academic publications, industry reports, and secondary data. Findings reveal that digitalization enhances UMKM competitiveness through global market access, operational efficiency, and product innovation. However, significant barriers persist, including the digital divide, low technological literacy, and inadequate infrastructure, which disproportionately affect rural and resource-constrained enterprises. The study underscores the necessity of multi-stakeholder collaboration to support UMKM transformation, with strategic recommendations focusing on enhancing digital literacy programs, investing in scalable technological infrastructure, and formulating inclusive policies. These measures are critical to ensuring UMKM sustainability and equitable participation in the global digital economy.